1997
DOI: 10.1093/clinids/24.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cutaneous Leishmaniasis with Allopurinol and Stibogluconate

Abstract: We conducted a randomized, controlled study in southern Colombia to determine if the addition of allopurinol to stibogluconate was superior to stibogluconate alone in the treatment of cutaneous leishmaniasis. Lesions that healed after a 3-month course of therapy and remained so during a 1-year period of follow-up were considered cured. The cure rate for patients treated with stibogluconate was 39%; the addition of allopurinol increased this rate to 71% (P = .005). For the treatment of cutaneous leishmaniasis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…Published efficacy trials of pentavalent antimonial drugs using a regimen of 20 mg Sb/kg/d for 20 days in Colombia and the Americas, have documented an efficacy of 88 to 100% for the treatment of cutaneous leishmaniasis caused by species of the Leishmania Viannia subgenus. 5,8,[13][14][15][16]20 One group in the Colombian southwest and close to our study area, reported efficacy of meglumine antimonate with a 15-day regimen, to be 40%, 21,22 and close to the 36-37% efficacy of placebo reported by other investigators in other areas of Colombia. 8,20 All of these trials have involved young-adult populations primarily.…”
Section: Discussionsupporting
confidence: 83%
“…Published efficacy trials of pentavalent antimonial drugs using a regimen of 20 mg Sb/kg/d for 20 days in Colombia and the Americas, have documented an efficacy of 88 to 100% for the treatment of cutaneous leishmaniasis caused by species of the Leishmania Viannia subgenus. 5,8,[13][14][15][16]20 One group in the Colombian southwest and close to our study area, reported efficacy of meglumine antimonate with a 15-day regimen, to be 40%, 21,22 and close to the 36-37% efficacy of placebo reported by other investigators in other areas of Colombia. 8,20 All of these trials have involved young-adult populations primarily.…”
Section: Discussionsupporting
confidence: 83%
“…7 CF cure rates attained with the use of pentavalent antimony were compatible to those found by other authors. 14,22,23 In the case of MCF, these rates were smaller, thus reaffirming the greater difficulty found in the treatment of this form of the disease (Table 1). Results indicating otherwise might be derived, for instance, from methodologies different than the one employed in this study.…”
Section: Resultsmentioning
confidence: 71%
“…Current evidence indicates that purine analogues alone or in combination with other chemotherapeutic agents are very effective against almost any fast-growing cells (22,41). Allopurinol, a purine analogue, has been used to treat leishmaniasis alone (34,48) or combined with other drugs (21,35,36,39,47). It should be pointed out, however, that the efficacy of allopurinol monotherapy remains unclear.…”
Section: Discussionmentioning
confidence: 99%